Effect of metformin treatment on inflammatory markers in type 2 diabetes mellitus—A systematic review and meta-analysis - Renuka Suvarna, Revathi P. Shenoy, M. Mukhyaprana Prabhu, Guruprasad Kalthur, Basavaraj S. Hadapad, Varashree Bolar Suryakanth (Journal of Applied Pharmaceutical Science, 2022)
Background: Inflammatory markers have a crucial role in the development and pathogenesis of type 2 diabetes mellitus (T2DM). Therefore, an ideal treatment for T2DM should exert multidimensional beneficial effects for the management of diabetes. Metformin, being a first-line therapy for T2DM, has proved to have an excellent hypoglycemic effect, but the conclusion of its effect on inflammation is inconsistent. This study aims to evaluate the pooled effect of metformin on inflammatory markers in T2DM.Methods: PubMed, CINHAL, and Scopus were searched systematically, and the references were further explored for eligible articles. 28 articles were extracted from 2,514 studies after eligibility screening based on the selection criteria. The data of inflammatory markers were then analyzed for meta-analysis in RevMan software.Results: The result of the subgroup meta-analysis shows that C-reactive protein (CRP) and high sensitivity C-reactive protein proved to be statistically significant for metformin in the placebo compared group. However, interleukin-6 and adiponectin proved to be beneficial for the comparator group.Conclusion: It is important to understand the validated effect of metformin on inflammatory markers in T2DM, which is possible by following an appropriate and universal assessment method with a uniform time and dose of metformin.Systematic Review Registration: The protocol for this systematic review is registered with PROSPERO (CRD42020180403).
Keywords: Metformin, inflammatory markers, metformin treatment, type 2 diabetes mellitus